A comparative evaluation of dexmedetomidine and fentanyl with ropivacaine (0.75%) for epidural anesthesia in lower limb orthopedic surgery - Parashar, Preeti; Sharma, Manoj Kumar; Sakhareliya, Tushar; Raval, Dipak L. (International Journal of Research in Medical Sciences, 2021)
Background: The aim of the study was to compare sensory and motor block characteristics, sedation score, post-operative analgesia and hemodynamic changes following epidural ropivacaine 15 ml (0.75%) supplemented with either dexmedetomidine (1 µg/kg) or fentanyl (1 µg/kg) in lower limb orthopedic surgery. Methods: The study was conducted in 60 patients of either sex belonging to ASA status I , II or III, aged 20 to 60 years undergoing lower limb orthopedic surgeries. In this prospective, randomized controlled study patients were divided into two different groups. Group RD receiving dexmedetomidine 1 mcg/kg+15 ml ropivacaine (0.75%) and group RF receiving fentanyl 1 mcg/kg+15 ml ropivacaine (0.75%). Each group included 30 patients. Results: The onset of sensory analgesia at shin of tibia was significantly early with dexmedetomidine (251.7±131.9 secs) as compared to fentanyl (503±63 secs) and similarly the onset of motor block was significantly early in group RD (533±239.6 secs) as compared to group RF (712.66±90.25 secs). Time for complete motor blockade was also significantly faster with group RD (57.1±5.1 mins) as compared to (61.5±3.2 mins) in group RF. The mean time for two segment regression was 274.3±43.6 mins in group RD, while 243.2±19.2 mins in group RF which was statistically significant (p<0.05). The decrease in heart rate, systolic, diastolic blood pressure and mean arterial blood pressure was significantly more in group RD as compared to RF. Conclusions: Addition of dexmedetomidine to epidural ropivacaine produces rapid onset of sensory and motor blockade, prolonged duration of analgesia, with better hemodynamic stability as compared to fentanyl, hence being a useful alternative adjuvant.